HEALTH EDUCATION IN THE PREVENTION OF WORM INFESTATION USING BOOKLETS FOR TODDLERS - Riadi, Dela; Hadiwiardjo, Yanti Harjono; Hasibuan, Syarif Rahman; Pradnyani, Putu Erma; Kristanti, Melly; Saputra, Dwi Arwandi Yogi; Aprilicia, Gita (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
In Indonesia, soil-transmitted worm infestation remains a serious public health problem, especially for young children. The high incidence of worms increases the risk of stunting, anemia, and malnutrition in children. Prevention efforts are hampered by low public awareness and the belief that worms are not a serious disease. The objective of this community service project is to educate mothers of toddlers and Integrated Health Post cadres about worm prevention. Counselling and health education through booklets are among the techniques used at integrated health post Kemuning A, Ratu Jaya Community Health Center. Participants in this activity consisted of 17 mothers of toddlers and 9 cadres from the integrated health post. On December 17, 2025, the activity was carried out through counselling, discussions, and a question-and-answer session. The results of a qualitative evaluation showed that mothers' awareness of risk factors and how to prevent worms had increased, as had the cadres' knowledge, awareness, and confidence in educating the community. It was concluded that by using Integrated health post-based education strategies, this program succeeded in empowering the community to prevent worms in toddlers.